Changeability of posterity of different morphological parts of winter wheat ear according to quantitative signs - Баган, А. В.; Юрченко, С. О.; Шакалій, С. М. (Scientific Progress & Innovations, 2012)
Quantitative signs of posterity of top part, middle part and bottom part of winter wheat ear are analyzed The level of ear length variation, quantity of ears and grains from an ear, mass of ear with grains, 1000 grains mass are established by posterity of different morphological ear parts of examined varieties. Effectiveness of soft winter wheat genotype selection according to ear length and ears quantity is pointed out. The posterity of the middle part of winter wheat varieties is sorted out by productivity and low level of quantitative signs variation.